La narrativa de los sordos como base para la construcción de una pedagogía vivencial - Muñoz Vilugrón, Karina (2024)
The cultural-linguistic education of the deaf has been minimally incorporated into the Chilean educational system. It has only been in the past decade that deaf adults have been included in classrooms with didactic approaches centered on hearing culture. This research aims to investigate deaf narratives to develop a pedagogical proposal grounded in deaf epistemologies. A semi-structured interview was conducted with 15 deaf individuals using Chilean Sign Language. The data collected was analyzed using Atlas.ti software, employing open and axial coding. The findings indicate that a pedagogical approach for the deaf should encompass the following elements: deaf identity, Chilean Sign Language, and a safe educational environment. The conclusions suggest that these pedagogical proposals should integrate a pedagogy with a deaf experiential perspective.